Desenvolvimento, descentralização da gestão ambiental e licenciamento na Amazônia: aplicação da análise institucional ao caso do município de Laranjal do Jari (AP) - RIBEIRO, Mário Sérgio dos Santos (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2021)
The relationship between development, decentralization of environmental management and licensing brings to the debate the challenges of the municipality in becoming an agent that promotes sustainable practices. For Amazonian states, such as Amapá, environmental decentralization has significant importance for its socio-environmental dynamics, enormous biodiver sity and contradictions and conflicts in the use of natural resources. It is necessary to think the territory in its multiple scales, problematizing the place. In this sense, the objective of the article is to analyze the practical experience of decentralized environmental management happened in the municipality of Laranjal do Jari (AP), with main focus on the instrument of en vironmental licensing. The methodology used was the application of the theoretical institutionalist approach to a case study, unfolded in a bibliographical survey, interviews and data collection. It is concluded that for the effectiveness of environmen tal licensing and other instruments, it is necessary to have political stability in the city hall and the local environmental agen cy and the search for policies and tools to strengthen local environmental management.